THE EFFECT OF ECONOMIC GROWTH ON THE UNEMPLOYMENT RATE IN MEDAN CITY 2017-2023 - Anggun Aiza Yolanda; Annisa Aulia; Yeni Susanti (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This study analyzes the effect of economic growth on the unemployment rate in Medan City for the period 2017-2023 using secondary data from the Central Statistics Agency (BPS) and using simple linear regression analysis. The results of the analysis show a negative relationship between economic growth and the unemployment rate, but the effect is not statistically significant (p>0.05). The t-test shows a significant constant, but the economic growth coefficient is not significant. The F test also shows that the overall regression model is not significant (p>0.05). The R-square of 0.463 indicates that the model only explains 46.3% of the variation in the unemployment rate, the rest is influenced by other factors. Economic growth in Medan City for that period did not have a significant effect on the unemployment rate. Other factors such as the quality of education, workforce training, infrastructure, and business incentives need to be considered to reduce unemployment. The government needs to increase quality economic growth and improve factors supporting employment.